Case Report: Infantile-Onset Fulminant Type 1 Diabetes Mellitus Caused by Novel Compound Heterozygous LRBA Variants - Totsune, Eriko; Nakano, Tomohiro; Moriya, Kunihiko; Sato, Daichi; Suzuki, Dai; Miura, Akinobu; Katayama, Saori; Niizuma, Hidetaka; Kanno, Junko; van Zelm, Menno C.; Imai, Kohsuke; Kanegane, Hirokazu; et al. (Frontiers in Immunology, 2021)
Lipopolysaccharide-responsive beige-like anchor (LRBA) deficiency is a subtype of common variable immune deficiency (CVID). Numerous case reports and cohort studies have described a broad spectrum of clinical manifestations and variable disease phenotypes, including immune dysregulation, enteropathy, and recurrent infections. Although LRBA deficiency is an autosomal recessive primary immunodeficiency resulting in a phenotype similar to CVID, it is a monogenic disease and separate from CVID. Recently, in a report of monogenic primary immunodeficiency disorder associated with CVID and autoimmunity, the most common mutated gene was LRBA. We report the case of a girl who presented with fulminant type 1 diabetes at age 7 months. She later experienced recurrent bacterial infections with neutropenia and idiopathic thrombocytopenic purpura. Clinical genome sequencing revealed compound heterozygosity of the LRBA gene, which bore two novel mutations. A genetic basis should be considered in the differential diagnosis for very young patients with fulminant autoimmunity, and the diagnostic work-up should include evaluation of markers of immunodeficiency.